Edukasi Tentang Pencegahan dan Penanganan Dermatitis Tangan Sebagai Dampak Kebiasaan Hand Hygiene Pada Tenaga Kesehatan Unit Rawat Jalan Rumah Sakit Universitas Mataram - Dedianto Hidajat; Niti Wedayani; Novia Andansari Putri R (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Hand hygiene performed by health workers has an important role in preventing infection and virus transmission. Unfortunately, frequent hand hygiene measures can cause various changes in skin texture, ranging from the development of skin xerosis (dry skin) to irritant contact dermatitis (DKI) or, even, allergic contact dermatitis (DKA). Research at one of the COVID-19 referral type B hospitals in Mataram, West Nusa Tenggara showed a significant relationship between knowledge, attitudes and behavior towards the incidence of hand dermatitis in health workers working at the hospital. Although it does not cause death, the increasing incidence of hand dermatitis will reduce the productivity, performance and quality of life of sufferers. Therefore, we will provide education in the form of providing counseling as well as identifying the determinants of knowledge, attitudes and behavior of health workers in the outpatient unit of UNRAM Hospital on the prevention and treatment of hand dermatitis due to hand hygiene measures The approach steps taken in this program are counseling or providing education to visitors to the skin and genital polyclinic at the Mataram University Hospital. In 12 respondents there were 6 (50%) respondents experienced hand dermatitis and 6 (50%) respondents did not experience hand dermatitis. Knowledge and behavior of health workers at the Mataram University Hospital regarding hand hygiene are not related to the incidence of hand dermatitis.